The woman in the library : a novel - Gentill, Sulari (Poisoned Pen Press, 2022)
"The beautifully ornate reading room at the Boston Public Library is completely silent one weekday morning, until a woman's terrified scream echoes through the room. Security guards immediately appear and instruct everyone inside to stay put until they determine there is no threat. While they wait for the all-clear, four strangers who had been sitting in the reading room get to chatting and quickly become friendly. Harriet, Marigold, Whit, and Caine each have their own reasons for being in the reading room that morning--and it just happens that one of them may turn out to be a murderer. For readers of Midnight at the Bright Ideas Bookstore, with shades of The Secret History, THE WOMAN IN THE LIBRARY is an unexpectedly twisty literary adventure that examines the complicated nature of friendship and shows us that words can be the most dangerous weapons of all"--